Interleukin-23 receptor gene polymorphisms in osteoporosis - Ulutaş, Firdevs; Çetin, Ozan; Çobankara, Veli (The European Research Journal, 2023)
Objectives: Osteoporosis (OP) is a usual disease with a possible genetic predisposition. IL-23 plays a role in physiological bone remodeling and regulates the activity of cells of the bone either directly or indirectly on bone-resorbing osteoclasts as well as on bone-forming osteoblasts. Recent animal and human trials have revealed the main pro-osteoclastogenic activities for the IL-23 pathway. We examined nine single nucleotide polymorphisms (SNPs) in the interleukin-23 receptor (IL-23R) in 100 OP patients and gender- and age-matched 96 healthy volunteers. The most analyzed SNPs in the recent rheumatology literature were selected. Methods: In addition to gene polymorphisms several laboratory parameters (osteocalcin, parathormone, vitamine D) were investigated. Independent Samples t-test and Mann-Whitney-U test were used to compare several demographic and clinical parameters between the groups. P-value < 0.05 was accepted to be statistically significant. Results: Having the heterozygous GA genotype of IL-23R rs1004819 and the heterozygous CT genotype of Il-23R rs7530511 significantly increase the risk of developing OP (adjusted OR: 3.51, p = 0.031 and OR: 2.41, p = 0.027, respectively). The wild homozygous GG genotype of Il-23R rs11209032 had higher osteocalcin levels compared with the mutant homozygous AA genotype (18.75 ± 9.76, p = 0.009). Conclusions: Our findings suggest that several IL-23R gene polymorphisms are seen more often in osteoporosis patients than in healthy volunteers. In addition, some SNPs were related to higher serum osteocalcin levels.